Racism in football: perspectives from two sides of the Atlantic - Kassimeris, Christos (Hate crime in football, 2023)
Racism in football has, evidently, quite a long history. Whether in the form of mimicking monkey sounds, throwing bananas at Black players or generally abusing non-White footballers, racism has almost become common practice in and around football stadiums in many countries across the world. Better known today as ‘hate crime’, and certainly a part of national legislation and international statutes, the many different shapes and forms of racial discrimination that continue to blemish the popular game of football are often easily identifiable, whether they be actions carried out within the anonymity that characterizes a crowd of football supporters or the result of racist stereotypes held by the game’s senior officials. While national and international governing bodies, along with football clubs, officials and players, often condemn the phenomenon of racism in football, and the pertinent governing bodies all maintain regulations that stipulate specific penalties when relevant incidents occur, too little has been achieved. Since racial discrimination varies from one cultural setting to another, this chapter first assesses the official position of the Fédération Internationale de Football Association (FIFA), the Union of European Football Associations and the Confederation of North, Central America and Caribbean Association Football vis-à-vis racism in football. Then it examines race-related cases in English, American and Italian football. Our point of departure is FIFA’s Good Practice Guide on Diversity and Anti-Discrimination, for it explicitly states that ‘one racist comment … does not necessarily make a person racist’ (FIFA, nd: 91).